Marriage of Pregnant Women Out of Wedlock According to the Shafi'i School and Compilation of Islamic Law - Jamil, Jumrah; Murut, Risman; Soulisa, Muhammad Rizal; Labondu, Jan; M. Kasuba, Witri; Raman, Reny; Talib, Anwar (Formosa Journal of Applied Sciences, 2023)
The aim of this research is to develop a comparison. Regarding the KHI legal framework for marrying pregnant women out of wedlock, Law Number One of 1974 and Imam Syafi'i apply. This summarizes qualitative techniques with conversation-based data collection; Descriptive data processing is used in this research process. Research findings indicate a relationship. Laws between the legal framework for marriage, pregnant women at KHI, and Imam Syafi'i. Meanwhile, individuals who mate with pregnant women make a difference. KHI Law Number 1 of 1974, it is a man who impregnates a woman. marry him if the woman becomes pregnant out of wedlock. Meanwhile, according to Imam Syafi'i, marriage is the result of pregnancy out of wedlock. Legally, a woman who is pregnant may immediately marry. regardless of whether she married the man who conceived her or not.